2010
DOI: 10.1007/s11417-010-9093-4
|View full text |Cite
|
Sign up to set email alerts
|

Introduction: White-Collar and Corporate Crime in Asia

Abstract: In this introduction to this special issue of the Journal we broadly consider the problem of white-collar and corporate crime in Asia. Official reports from China show the pervasiveness of current problems and the inherent dangers underlying continued economic growth and reforms. We also consider evidence bearing on the idea that Japan's remarkably low rate of common crime is likely eclipsed by the level of white-collar and corporate crime, and briefly discuss the institutionalization of economic crime in Sout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Unethical practices were often discussed especially in organizational governance practices for several decades. It will hurt public confidence and hinder economic growth (Pontell and Geis, 2010). Whistleblowing has recognized by scholars and practitioners as an effective way to prevent and stop unethical practices in the organization (Cheng et al , 2017; Fredin et al , 2018; Liu et al , 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Unethical practices were often discussed especially in organizational governance practices for several decades. It will hurt public confidence and hinder economic growth (Pontell and Geis, 2010). Whistleblowing has recognized by scholars and practitioners as an effective way to prevent and stop unethical practices in the organization (Cheng et al , 2017; Fredin et al , 2018; Liu et al , 2016).…”
Section: Introductionmentioning
confidence: 99%
“…With the open-door policy and a deepening integration of China’s economy into the world economy, China has become an important player in the world economy, and meanwhile, a magnet for corporate crime. For example, in 2005, the Chinese government reported that there were 240 major criminal violations in China’s state-owned commercial banks in the first half of that year, accounting for one-third of the country’s total bank scandals and a total loss of ¥1.6bn (US$198m) (Pontell and Geis, 2010).…”
Section: Introductionmentioning
confidence: 99%